ANALYSIS OF POSTNASAL DRIP IN PATIENTS WITH CHRONIC SINUSITIS: EFFICACY OF A COMBINED THERAPY OF CARBOCISTEINE AND ERYTHROMYCIN IN THE TREATMENT OF CHRONIC SINUSITIS - Fukushima, Noriyuki; Tatsukawa, Takaharu; Hirakawa, Katsuhiro; Hirata, Shitau; Yajin, Koji (JIBI INKOKA TEMBO, 1999)
The clinical efficacy of a combined therapy for chronic sinusitis consisting of the administration of carbocisteine and erythromycin was assessed. Two regimens were compared : a combined therapy of carbocisteine and erythromycin (EC group), and the administration of only erythromycin (E group). The sialic acid (S) and fucose (F) concentrations in the postnasal drip of the subjects were analyzed before and after treatment. 1) Both the E group and the EC group showed an improvement in subjective and objective symptoms as well as X-ray opacity. Overall, the improvement was higher in the EC group (92.3%) than in the E group (77.8%). 2) Before treatment, subjects with severe cases of chronic sinusitis had high concentrations of sialic acid and fucose in their postnasal drip. In those cases showing an excellent response to treatment, the S/F ratio was reduced and the concentration of fucose increased after treatment. 3) The study suggests that a combined therapy of carbocisteine and erythromycin or of erythromycin alone is closely related to the S/F ratio in postnasal drip, and that both of these regimens offer benefits for the treatment of chronic sinusitis. Furthermore, the study suggests that the S/F ratio may be a useful index for evaluating the improvement of chronic sinusitis.